CARDIOTOXICITY OF HIGH-DOSE METHYLPREDNISOLONE IN PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKEMIA – A CASE REPORT - Apostolović Stojanović, Milica; Radojkovic, Milica; Stojanovic, Aleksandar; Vukomanovic, Vladan (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Several classes of drugs can cause atrial fibrillation (AF) in patients without heart disease, as well as the occurrence of AF in pre-existing heart disease. Drug-induced AF is most often clinically manifested in the form of paroxysms. High doses of intravenous methylprednisolone (HDMP) in the treatment of chronic lymphocytic leukemia (CLL) have been associated with the occurrence of various adverse effects, including AF. The exact mechanism of HDMP-induced AF is unknown. Case presentation: We present the case of a patient with CLL in whom AF occurred after the administration of a high dose of intravenous methylprednisolone. Conclusion: Physicians should be aware of the special circumstances in the treatment of CLL, because drug-induced AF can be a side effect that limits further therapy.